The amygdaloid modulation of adrenocortical function and habituation in rats - Saling, Michael Martin (My University, 2015)
The relationship between amygdaloid damage and the intmperitoneal injection of betamethasone was studied with respect to the exploratory behaviour of male hooded rats. Amygdalaetomy produced attenuated longterm habituation of stimulus-specific and general exploratory behaviour. This habituation deficit was uninfluenced by betamethasone. Betamethasone also failed to influence long-tori. habituation in the intact animals. Although amygdalectomy did not alter short-term habituation, betamethasone accelerated the short-term habituation of general exploratory behaviour in both amygdalectomised and intact animals. On replication of the experiment betamethasone administration failed to influence exploration. It was tentatively concluded that amygdalectomy and betamethasone influence the habituation of exploratory activity under mutually exclusive circumstances. However, the failure to replicate the amygdalectomy- and betamethasone- induced changes in habituation could not be inteipreted within the context of the present experiment.
A Dissertation Submitted to the Faculty oC Arts University of the Witwatersrand, Johannesburg for the Degree of Master of Arts Johannesburg, 1974
Keywords: Adrenal cortex; Rats